2013
DOI: 10.1073/pnas.1219888110
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of lipid antigen to macrophages via the CD169/sialoadhesin endocytic pathway induces robust invariant natural killer T cell activation

Abstract: Invariant natural killer T (iNKT) cells induce a protective immune response triggered by foreign glycolipid antigens bound to CD1d on antigen-presenting cells (APCs). A limitation of using glycolipid antigens to stimulate immune responses in human patients has been the inability to target them to the most effective APCs. Recent studies have implicated phagocytic CD169 + macrophages as major APCs in lymph nodes for priming iNKT cells in mice immunized with glycolipid antigen in particulate form. CD169 is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 40 publications
0
86
0
2
Order By: Relevance
“…Therefore, a controlled delivery of a-GalCer is a requisite to optimize iNKT cell responses. A recent study showed that specific targeting of a-GalCer to CD169 + macrophages leads to an efficient iNKT cell activation in vivo but fails to trigger transactivation of innate immune cells (42). The consequence on the recall response was not reported in the later study.…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, a controlled delivery of a-GalCer is a requisite to optimize iNKT cell responses. A recent study showed that specific targeting of a-GalCer to CD169 + macrophages leads to an efficient iNKT cell activation in vivo but fails to trigger transactivation of innate immune cells (42). The consequence on the recall response was not reported in the later study.…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 85%
“…Of interest, and in contrast with specific targeting of a-GalCer to CD169 + macrophages (42), active delivery of a-GalCer to CD8a + DCs also increased the transactivation of NK, gd T lymphocytes, and DCs. Thus, CD8a + DCs targeting via DEC205 optimizes the iNKT cell-mediated innate immune response in agreement with the fact that CD8a + DCs are a dominant source of bioactive IL-12 (26,49).…”
Section: Nps Incorporating A-galcer and Ag Protect Against Tumor Devementioning
confidence: 94%
“…Siglecs which lack an ITIM domain (such as Siglec-14, 15, and 16) associate with DAP12 via a positively charged amino acid in their transmembrane region to activate receptors through the recruitment of Syk (15,40). Siglec-1, the first discovered member of Siglecs, has been shown to play an important role in sialylated pathogen uptake (17,19,(53)(54)(55), antigen presentation (56,57), lymphocyte proliferation (58), self-tolerance (59,60) and antiviral immune response (47). However, the biological function of Siglec-1 in endotoxin tolerance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Siglec1 has been shown to play an important role in the capture and internalization of pathogens via binding to sialic acid residues expressed on the surface of some important pathogens such as HIV-1 [12] and porcine reproductive and respiratory syndrome virus [13]. Siglec1 has also been shown to participate in antigen presentation and induction of adaptive immune responses [14,15]. However, the biological functions of Siglec1 in antiviral innate immunity remain elusive, and its cytosolic signaling pathway is still unknown.…”
Section: Introductionmentioning
confidence: 99%